Costumized growth curves for intrauterine growth restriction diagnosis Optimization - Tipiani-Rodríguez, Oswaldo (2014)
Background: Fetuses with intrauterine growth restriction (IUGR) are at high risk of perinatal morbidity and mortality and there is much difficulty to differentiate fetuses with IUGR from those small for gestational age (SGA), because even Doppler ultrasound has limitations in this regard. It has been suggested that customized growth curves could shed light on this dilemma. Objectives: To design a customized growth curves software to optimize IUGR diagnosis at EsSalud. Design: Comparative, observational and descriptive study. Setting: Hospital Edgardo Rebagliati Martins (HNERM), EsSalud, Lima, Peru. Participants: Pregnant women and their fetuses and newborns. Methods: An intrauterine growth curve was constructed with ultrasound fetal measurements born and newborn weight recorded at HNERM and, based on this a customized growth curves software was designed. Student’s t, ANOVA and non-parametric tests were used. Differences were considered significant when p <0.05. Main outcome measures: Customized fetal growth curve. Results: We selected 29 239 newborns between 2003 and 2010. Neonatal weight was found to be influenced by maternal height, pre-gestational weight, maternal age (ANOVA: F= 3.8; F=214.7; and F=11.2 respectively; p<0,05), male fetal sex and multiparity (student t test, p<0,001). Software was designed based on these parameters for predicting fetal weight for each gestational week. Conclusions: Customized fetal growth curves software was designed in order to optimize IUGR fetuses’ diagnosis at Es- Salud.